2014
DOI: 10.1097/ypg.0000000000000044
|View full text |Cite
|
Sign up to set email alerts
|

The role of genetic variants in genes regulating the oxytocin–vasopressin neurohumoral system in childhood-onset aggression

Abstract: Genetic variants regulating the OXT-AVP system may be associated with childhood-onset aggression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 28 publications
0
21
1
1
Order By: Relevance
“…Genomic DNA was extracted from saliva, blood, and buccal cells using procedures outlined by Malik et al (2014). Manufacturer's protocol for TaqMan s SNP Assays (Life Technologies, Applied Biosystems Inc., Foster City, CA, USA) was used to genotype five SNPs in FKBP5, rs4713916, rs9470080, rs1360780, rs9296158, and rs3800373 (see Supplementary materials for detailed positions and procedures).…”
Section: Dna Collection and Genotypingmentioning
confidence: 99%
“…Genomic DNA was extracted from saliva, blood, and buccal cells using procedures outlined by Malik et al (2014). Manufacturer's protocol for TaqMan s SNP Assays (Life Technologies, Applied Biosystems Inc., Foster City, CA, USA) was used to genotype five SNPs in FKBP5, rs4713916, rs9470080, rs1360780, rs9296158, and rs3800373 (see Supplementary materials for detailed positions and procedures).…”
Section: Dna Collection and Genotypingmentioning
confidence: 99%
“…The genes for vasopressin and for the oxytocin and vasopressin receptors (AVP, OXTR, AVPR1A and AVPR1B) have been associated with aggression in children [Malik et al, 2012[Malik et al, , 2014Zai et al, 2012b;Luppino et al, 2014]. Oxytocin and vasopressin encode neurohypophysial hormones with primary roles in sexual reproduction and in water retention, respectively, but they have also Sakai et al [2006Sakai et al [ , 2007Sakai et al [ , 2010 SLC6A3 (DAT1) Solute carrier family 6 (neurotransmitter transporter), member 3 (dopamine transporter)…”
Section: Candidate Genes Studied In Children and Adolescentsmentioning
confidence: 99%
“…3 Because ADHD is related strongly with aggression, studies that showed the association between aggression and the vasopressin system may also indicate the possible role of vasopressin in ADHD. 30,31 On the other hand, both oxytocin and vasopressin are regarded as social hormones and are closely related neuropeptides; recent studies that reported relations between ADHD and the oxytocinergic system have also suggested the link between the vasopressinergic system and ADHD. 7,8 The present study found no significant difference between the ADHD and control groups for plasma vasopressin levels and could not provide any direct evidence concerning the possible role of vasopressin in ADHD.…”
Section: Discussionmentioning
confidence: 99%